Vowel Changes in Two RP Speakers with Different Social Status: A Sociophonetic Study of TRAP/STRUT Vowels - Hamid, Twana Saadi (Sulaimani Journal for Humanities, 2018)
This study tries to track and compare changes of TRAP/STRUT vowels in three time periods (1950s; 1980s and 2012). The vowel changes, from the Queen of England and David Attenborough, are analysed and compared for two reasons. First, to track and discover changes in RP vowel formants. Second, to see to what extent, if any, the two speakers of the study adapt their vowel formants to that of RP. To this end, Formant frequencies of TRAP/STRUT vowels for each speaker in each time period is extracted using PRAAT. Unlike Harrington et al (2000) who acoustically Journal of Zankoy Sulaimani-Part B / for Humanities No (58) Oct 2018 303 analyse The Queen’s Christmas speech, this study analyses and compares The Queen’s vowel formant changes with another RP speaker. By having two RP speakers with different social status and different gender (male and female), this study reports findings of social variables such as social class and gender.